Peran Al-Quran Sebagai Sumber Ilmu Pengetahuan: Kajian Interdisipliner - Ana Anisa; Heri Khoiruddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Quran, the holy book of Islam, has long been the focus of attention in the context of religion and spirituality. However, in recent decades, interest in the Quran as a potential source of science has increased. Previous studies have shown that the Quran contains knowledge relevant to various fields of modern science. This study aims to investigate the role of the Quran as a source of science in an interdisciplinary context. The main objective of this study is to analyze and identify elements in the Quran that have relevance in the development of modern science. In addition, this study also aims to understand how the Quran can make a positive contribution in expanding our understanding of the world and various aspects of life. This research uses an interdisciplinary method of analyzing Quranic texts. The author examines various Quranic verses related to scientific concepts and then compares them with recent scientific findings in various fields such as natural science, social science, and medical science. The results show that the Quran contains many verses that are relevant to recent scientific discoveries. Examples include descriptions of the creation of the universe, human development, and ethical principles relevant in science. The findings support the argument that the Quran can be considered a valuable source of science and can help enrich our understanding of the world we live in. This research has significant implications in supporting the dialogue between religion and science, as well as opening up the potential for closer collaboration between religious scholars and scientists in the exploration of science and spirituality.